Sagot :
Answer:
ans: 2( ×-5 )
Step-by-step explanation:
hope it helps
Answer:2x - 10 =
Simplifying
2x + -10 = 0
Reorder the terms:
-10 + 2x = 0
Solving
-10 + 2x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '10' to each side of the equation.
-10 + 10 + 2x = 0 + 10
Combine like terms: -10 + 10 = 0
0 + 2x = 0 + 10
2x = 0 + 10
Combine like terms: 0 + 10 = 10
2x = 10
Divide each side by '2'.
x = 5
Simplifying
x = 5
Step-by-step explanation:pa brainliest naman o